Management of Job Fair at Vocational High School: A Case Study in Tulungagung, Indonesia - Agus Munir; Yoto Yoto; Didik Nurhadi (Belantika Pendidikan, 2022)
This study will examine the planning of school-industry collaboration, labor distribution, and recruitment approaches. It also describes the supporting and hindering aspects of the BKK employment fair in distributing workers at VHS SORE Tulungagung and VHS 1 Rejotangan. This study employs a qualitative case study research method. This study employs observation, documentation, and interviews. The results reveal BKK exploring for industry contacts, selecting industries to work with, and collaborating. To distribute graduates, BKK registers them, arranges for them to be interviewed, and then sends them to work. Internship, school-industry, and industry-industry recruiting models. Moreover, schools and industries have provided sufficient infrastructure for BKK activities, whereas many parents do not allow their children to work outside the city.